Advances in cloning functional genes for rice yield traits and molecular design breeding in China - Zhong, Qianqian; Jia, Qiwei; Yin, Wenjing; Wang, Yuexing; Rao, Yuchun; Mao, Yijian (Frontiers in Plant Science, 2023)
Rice, a major food crop in China, contributes significantly to international food stability. Advances in rice genome sequencing, bioinformatics, and transgenic techniques have catalyzed Chinese researchers’ discovery of novel genes that control rice yield. These breakthroughs in research also encompass the analysis of genetic regulatory networks and the establishment of a new framework for molecular design breeding, leading to numerous transformative findings in this field. In this review, some breakthroughs in rice yield traits and a series of achievements in molecular design breeding in China in recent years are presented; the identification and cloning of functional genes related to yield traits and the development of molecular markers of rice functional genes are summarized, with the intention of playing a reference role in the following molecular design breeding work and how to further improve rice yield.